Urgent adaptive effects of a single intake of carbohydrate-electrolyte mixture with plant extracts in maintaining microcirculation parameters of highly qualified athletes - Tribrat, N. S.; Pogodina, S. V.; Biryukova, E. A.; Chuyan, E. N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the short-term adaptive effects of a single dose of a carbohydrate-electrolyte mixture with plant antioxidants (CEMA) in maintaining the microcirculation system using the example of highly qualified orienteers under the conditions of a two-stage bicycle ergometric test PWC170.